Intangible Space of Continuity and Changes in Ondel-Ondel’s Costume Elements and Performance - Wahidiyat, Mita Purbasari; Carollina, Donna; Marianto, Martinus Dwi; Triatmodjo, Suastiwi (Bina Nusantara University, 2024)
The research discussed Ondel-ondel, a significant and tall doll from Betawi, since the costume elements could be changed anytime, anywhere, and in any shape, Ondel-ondel appeared more alive and appealing in different looks. Initially, Ondel-ondel seemed too unchanged, but it was prettier than before. There were many Ondel-ondel performances in Jakarta's streets that were not accompanied by music. Ondel-ondel transformed not only the costumes but also the myth from repellent to entertainer. The changes were exciting to discover the concept or idea of its background, relationships, impacts on the environment, and other meanings for society. The research applied a descriptive qualitative method. Based on a historical approach with semiotic analysis and interpretation as a research method, Ondel-ondel costume elements underwent continuity and changed alongside the social, political, economic, and cultural contexts linked to the role of power of its respective time. Within the continuity and changes in each Ondel-ondel model, there was a compromise and social dynamic in society, which gave the costume elements a unique trade. This compromise created a cultural negotiation space in the community and helped to develop a typical environment that distinguished itself from others. The result is four Ondel-ondel models, each representing society's compromise and the social dynamic between the authorities, the community, and the Ondel-ondel players. When the transformation of the ondel-ondel's appearance creates an intangible space between maintaining its ideology. Meanwhile, on the other hand, the changes in ondel-ondel portray how the changing times also alter the appearance of the ondel-ondel.